Cloud point extraction of 2,4−dichlorophenol from aqueous samples employing β−cyclodextrin - Zain, N.N.M.; Abu Bakar, N.K.; Mohamad, Sharifah (Taylor & Francis, 2016)
In this study, β−cyclodextrin (β−CD) was used to enhance the extraction of 2,4−dichlorophenol (2,4−DCP) from the aqueous sample in cloud point extraction (CPE) using spectrophotometric method. Several parameters have been investigated with and without the presence of β−CD modifier, such as pH, equilibration temperature, analyte concentration, and water content in the CPE and CPE−βCD systems, respectively. Equilibrium data are described by the Langmuir isotherm in both CPE systems with and without β−CD modifier. The thermodynamic parameters (positive values of ΔH° and ΔS°, negative values of ΔG°) indicate that the solubilization of 2,4−DCP in a polyethylene glycol silicone surfactant (DC193C) is endothermic, entropy gained, and spontaneous in both systems. In the CPE−βCD system, the results show that the β−CD modifier is capable of enhancing the extraction of 2,4−DCP pollutant from aqueous samples.